Analisis Keamanan Sistem Informasi Berdasarkan Framework COBIT 5 Menggunakan Capability Maturity Model Integration (CMMI) - Umar, Rusydi; Riadi, Imam; Handoyo, Eko (Universitas Diponegoro, 2019)
Information technology is a very important part of a company or institution. The information system itself is expected to provide better benefits for companies or institutions. However, along with technological developments are often misused by some irresponsible parties that can lead to threats of the use of technology. Information system security is very important for institutions to maintain information optimally and safely. The existence of a security problem triggers a procedure to control access rights in an information system. A good information system is an information system that can be assessed at a security level, so that it can provide comfort for users. COBIT 5 as an information technology security control standard. Whereas to achieve the standard level of achievement CMMI is needed in information technology security. The combination of the two standards in the information system is able to provide a level of achievement of information technology. The results obtained from the maturity value are 4,458 which means the institutions are at the Managed and Measurable level. This level, institutions are increasingly made aware of technological developments. Institutions have implemented the quantification concept in each process, and are always monitored and controlled for performance. Information system security at this level is good, it's just that it still needs innovation and development to be ready, fast and right in handling security threats.